The application of chunking technique combined with writing is thinking to improve the communication skills - Sirniawan, Sirniawan; Hala, Yusminah; Jamaluddin, Asham Bin (Jurnal Mangifera Edu, 2025)
The student's cognitive load is high, and the level of thinking and communication skills is low. So, the chunking technique combined with writing thinking is implemented. The purpose of this study was to determine the difference in communication skills of students of circulatory system material taught with chunking techniques combined with writing is thinking, chunking techniques, and lecture techniques in class XI students of SMA Negeri 20 Gowa in the 2024/2025 school year. This type of research includes experiments in the form of a pretest, posttest, and nonequivalent control group design. Sampling technique with purposive sampling with specific consideration in the form of almost the same initial ability of students from three treatment classes where class XI. 1 (experimental class), XI.2 (positive control class), and XI.3 (negative control class), each of which totaled 30 students. Data acquisition using non-test instruments to see students' communication skills and teaching module implementation sheet. Hypothesis testing uses the Anacova test because the data is normally distributed and homogeneous. The results of hypothesis testing showed that the significance value was <0.000. This shows the sig value < α (0.05), so it can be concluded that H0 is rejected and H1 is accepted. This means that there are differences in the communication skills of students who are taught with chunking techniques combined with writing thinking (experimental class), chunking techniques (positive control class), and lecture techniques (negative control class) on human circulatory system material.